2D/2D Black Phosphorus/Nickel Hydroxide Heterostructures for Promoting Oxygen Evolution via Electronic Structure Modulation and Surface Reconstruction (Adv. Energy Mater. 25/2022). Issue 25 (7th July 2022) - Mei, Jun; Shang, Jing; He, Tianwei; Qi, Dongchen; Kou, Liangzhi; Liao, Ting; Du, Aijun; Sun, Ziqi
Abstract : Oxygen Evolution Reaction In article number 2201141, Jun Mei, Ziqi Sun and co‐workers design a 2D/2D heterostructured electrocatalyst by coupling mildly oxidized black phosphorus with 2D nickel hydroxide to reach a favorable electronic structure and a desired reconstructed surface structure towards high‐performance alkaline oxygen evolution reaction catalysis.